2022
DOI: 10.1007/s00300-022-03006-7
|View full text |Cite
|
Sign up to set email alerts
|

Can heat shock protein 70 (HSP70) serve as biomarkers in Antarctica for future ocean acidification, warming and salinity stress?

Abstract: The Antarctic Peninsula is one of the fastest-warming places on Earth. Elevated sea water temperatures cause glacier and sea ice melting. When icebergs melt into the ocean, it “freshens” the saltwater around them, reducing its salinity. The oceans absorb excess anthropogenic carbon dioxide (CO2) causing decline in ocean pH, a process known as ocean acidification. Many marine organisms are specifically affected by ocean warming, freshening and acidification. Due to the sensitivity of Antarctica to global warmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 168 publications
(210 reference statements)
0
10
0
Order By: Relevance
“…These interactions between HIF1a and HSPs could explain the cross-stress tolerance between heat and hypoxia [77][78][79]. HSPs have also been shown to play an essential role in the response of marine species to acidification (as reviewed by Yusof et al [80]). Therefore, the expression of transcription factors activating HSP genes and, thus, upregulation of HSPs during heatwaves could have also been beneficial for the performance of A. rubens in response to the applied upwelling event.…”
Section: (D) Sublethal Heatwaves May Induce Resistance To Upcoming Up...mentioning
confidence: 99%
“…These interactions between HIF1a and HSPs could explain the cross-stress tolerance between heat and hypoxia [77][78][79]. HSPs have also been shown to play an essential role in the response of marine species to acidification (as reviewed by Yusof et al [80]). Therefore, the expression of transcription factors activating HSP genes and, thus, upregulation of HSPs during heatwaves could have also been beneficial for the performance of A. rubens in response to the applied upwelling event.…”
Section: (D) Sublethal Heatwaves May Induce Resistance To Upcoming Up...mentioning
confidence: 99%
“…The presence of 9 SNPs within three heat shock proteins belonging to the highly conserved Hsp70 family of chaperone proteins contributed to enrichment of these GO categories ( Gupta et al, 2010 ): Hsc70-3 , Hsc70-4 , and Hsc70-5 ( The UniProt Consortium et al, 2021 ) ( Figure 6 , Supplementary Table S1 ). Heat shock proteins respond to protein damage caused by oxidative stress following exposure to a diverse set of environmental stressors ( Feder and Hofmann, 1999 ; reviewed in Gupta et al, 2010 ), and the related gene Hsp70 has been linked to response to heavy metal stress in bacteria, plants, nematodes, and fish ( Williams et al, 1996 ; Arts et al, 2004 ; Roh et al, 2006 ; reviewed in Gupta et al, 2010 ; Cui et al, 2013 ; Cui et al, 2019 ; Zuily et al, 2022 ) prompting its assessment for use as a bioindicator of pollution, environmental contamination, and climate change ( Pyza et al, 1997 ; Mukhopadhyay et al, 2003 ; Arts et al, 2004 ; Roh et al, 2006 ; Yusof et al, 2022 ). We recently reported an increase in expression of Hsc70-3 and Hsc70-5 in adult D. melanogaster females from the DSPR in response to copper stress ( Everman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of seven stress-related proteins belonging to the class of heat shock protein 70 (HSP70) family were significantly altered in deep-sea mussel gills of both Cdexposure groups. HSP70 is a group of highly conserved and abundant proteins that help organisms deal with abiotic stressors (heat shock, salinity change, acidification and contaminants) by refolding, sorting, translocating, and degrading deformed proteins, as well as being cochaperones and regulating the biologically active form of other proteins (Kim and Schöffl, 2002;Chaudhary et al, 2019;Yusof et al, 2022). A field investigation of deep-sea mussel Bathymodiolus azoricus from Atlantic hydrothermal vents confirmed that that this species could express and induce a mixture of constitutive heat-shock protein isoforms, ranging from 64 and 76 kDa, enabling it to survive despite toxic vent fluids (Pruski and Dixon, 2007).…”
Section: Stress Response Associated With CD Exposurementioning
confidence: 99%